Associations of Smartphone Ownership with Health-Related Quality of Life and Social Connectedness Among Older Japanese Adults: A Quantile Regression Analysis - Takashi Kawano; Goro Moriki (Social Sciences, 2026)
Loneliness and social isolation in later life are important public health concerns, and information and communication technology (ICT) may support everyday functioning and social participation among older adults. However, mean-based analyses may obscure variation in associations across outcome distributions. Using quantile regression, we examined the associations of smartphone ownership with health-related quality of life (SF-36v2: PCS, MCS, and RCS) and social connectedness (LSNS-6) among 919 community-dwelling senior club members in a regional Japanese city; regression analyses used 839 complete cases. Coefficients were estimated at the 20th, 40th, 60th, and 80th conditional quantiles. Smartphone ownership was associated with RCS at the 20th (β = 3.72), 40th (β = 4.42), and 60th (β = 2.21) quantiles, but not at the 80th quantile (β = 1.41), and coefficients differed significantly across quantiles (F(3, 3353) = 3.97, p = 0.008). The 20th-, 40th-, and 60th-quantile coefficients and the Wald test remained significant after Holm adjustment. Smartphone ownership was not associated with PCS, MCS, or LSNS-6 at any quantile. The smartphone ownership × gender interaction for RCS was non-significant at all quantiles, providing no evidence that this association differed by gender. These findings indicate that the association between smartphone ownership and role/social functioning varies across its conditional distribution. Because the study is cross-sectional and actual smartphone use was not measured, causal interpretation is not warranted. Longitudinal studies measuring patterns of smartphone use are needed.